Mechanism of Sugar-Induced Behavioral Effects - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The adrenomedullary response to a standard oral glucose load (1.75 gm/kg; maximum, 120 gm) and susceptibility to neuroglycopenia (assessed by the hypoglycemic clamp and measurements of P300 auditory evoked potentials [AEP]) were studied in 25 healthy children (8-16 years of age) compared to 23 young adults at the Children's Clinical Research Center, Yale University School of Medicine, New Haven, CT.